Gradual hypertension induction in middle‐aged Cyp1a1‐Ren2 transgenic rats produces significant impairments in spatial learning - Mari N. Willeman; Monica K. Chawla; Marc A. Zempare; Lauren A Biwer; Lan T. Hoang; Ajay R. Uprety; Megan C. Fitzhugh; Matthew De Both; Paul D. Coleman; Theodore P. Trouard; Gene E. Alexander; Kenneth D. Mitchell; et al. (Physiological Reports, 2019)
Abstract Hypertension is a major health concern in the developed world, and its prevalence increases with advancing age. The impact of hypertension on the function of the renal and cardiovascular systems is well studied; however, its influence on the brain regions important for cognition has garnered less attention. We utilized the Cyp1a1‐Ren2 xenobiotic‐inducible transgenic rat model to mimic both the age of onset and rate of induction of hypertension observed in humans. Male, 15‐month‐old transgenic rats were fed 0.15% indole‐3‐carbinol (I3C) chow to slowly induce renin‐dependent hypertension over a 6‐week period. Systolic blood pressure significantly increased, eventually reaching 200 mmHg by the end of the study period. In contrast, transgenic rats fed a control diet without I3C did not show significant changes in blood pressure (145 mmHg at the end of study). Hypertension was associated with cardiac, aortic, and renal hypertrophy as well as increased collagen deposition in the left ventricle and kidney of the I3C‐treated rats. Additionally, rats with hypertension showed reduced savings from prior spatial memory training when tested on the hippocampus‐dependent Morris swim task. Motor and sensory functions were found to be unaffected by induction of hypertension. Taken together, these data indicate a profound effect of hypertension not only on the cardiovascular‐renal axis but also on brain systems critically important for learning and memory. Future use of this model and approach may empower a more accurate investigation of the influence of aging on the systems responsible for cardiovascular, renal, and neurological health.